LA HISTORIA CULTURAL EN EL SALVADOR: UN CAMPO DE ESTUDIO EN CIERNES - Gregorio López , Carlos (2006)
This article analyzes the cultural history in El Salvador, which seems to be extremely optimistic, despite the fact that history is not a preferred field in El Salvador. The overall balance shows the historiographic deficiencies faced by this country. These deficiencies become more evident when working in a specific field of history. The article has a preliminary nature that procures dialogue and urges historians to search a development to understand and overcome these flaws.